2016
DOI: 10.1128/aem.02489-15
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Kinetics and Mechanism of a Human Norovirus Surrogate on Stainless Steel Coupons via Chlorine Dioxide Gas

Abstract: e Acute gastroenteritis caused by human norovirus is a significant public health issue. Fresh produce and seafood are examples of high-risk foods associated with norovirus outbreaks. Food contact surfaces also have the potential to harbor noroviruses if exposed to fecal contamination, aerosolized vomitus, or infected food handlers. Currently, there is no effective measure to decontaminate norovirus on food contact surfaces. Chlorine dioxide (ClO 2 ) gas is a strong oxidizer and is used as a decontaminating age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…This effect was significant in NoV GI and GII for the two ClO 2 concentrations tested, whereas it was significant in HAstV only for the highest disinfectant concentration (11 mg L −1 ). Wigginton et al (2012) and Sigstam et al (2013) reported extensive degradation of viral proteins by ClO 2 , while Yeap et al (2016) showed that ClO 2 inactivation of murine norovirus included disruption of viral structure.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was significant in NoV GI and GII for the two ClO 2 concentrations tested, whereas it was significant in HAstV only for the highest disinfectant concentration (11 mg L −1 ). Wigginton et al (2012) and Sigstam et al (2013) reported extensive degradation of viral proteins by ClO 2 , while Yeap et al (2016) showed that ClO 2 inactivation of murine norovirus included disruption of viral structure.…”
Section: Resultsmentioning
confidence: 99%
“…8 Although murine norovirus has outstanding environmental stability, a greater than 5 log 10 reduction has been achieved by using a ClO 2 gas dose of 24 ppm-h at 85% RH. 44 In contrast, vegetative bacteria such as Escherichia coli and Staphylococcus aureus showed a greater than 5 log 10 and greater than 2 log 10 reduction, respectively, with a total ClO 2 gas dose of 0.25 ppm-h at 52% RH. 26 A direct comparison of the exposure doses mentioned above is not possible because the RH varied in each report; the general trend is consistent with the principle of a hierarchy in chemical germicidal resistance.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, 0.03 ppm of ClO 2 has been indicated to prevent aerosol-induced influenza A virus by denaturing the envelope proteins of the virus [12] . The mechanism of norovirus inactivation by ClO 2 is attained through degradation of viral protein, including viral genomic RNA and disruption of viral strucutre [15] . In addition, an observation on ClO 2reduced lysozyme activities showed the potential role of ClO 2 in denaturation and degradation of protein using Raman spectroscopy and gel electrophoresis [16] .…”
Section: Mechanisms Behind the Efficacy Of Clo 2 Against Microbesmentioning
confidence: 99%
“…However, concentrations of ClO 2 equal to or more than 0.6 mg/L are required for a complete inactivation of viruses such as hepatitis A viruses, Norwalk and Norwalk-like viruses [19] . A 3-log reduction in murine norovirus 1 (MNV-1) was found when stainless steel contact surfaces were treated with ClO 2 gas at 2 mg/L for 5 minutes and 2.5 mg/L for 2 minutes while a complete virus inactivation was shown in a 1minute treatment with 4 mg/L of ClO 2 gas [15] . Although free residues of chlorine over a concentration of 2.19 mg/L of ClO 2 in wastewater do not entirely inactivating E. coli and f2 phage, it is able to completely inactivate SARS-CoV [20] .…”
Section: Revisit the Literaturementioning
confidence: 99%